The effects of a heating pad on anxiety, pain, and distress during urodynamic study in the female patients with stress urinary incontinence. Issue 3 (8th March 2018) - Kim, Jong Wook; Kim, Hyun Ju; Park, Young Joo; Kang, Sung G.; Park, Jae Y.; Bae, Jae Hyun; Kang, Seok Ho; Park, Hong Seok; Moon, Du Geon; Cheon, Jun; Lee, Jeong Gu; Kim, Je Jong; et al.
Abstract : Aims: Although generally well tolerated, a urodynamic study is an unpleasant and stressful procedure for some patients. This study evaluated the effects of a heating pad on anxiety, pain, and distress during urodynamic studies in female patients with stress urinary incontinence. Methods: A total of 74 female patients with stress urinary incontinence who underwent a urodynamic study between May 2015 and October 2015 were randomized to either the experimental group using a heating pad ( n = 37) or control group ( n = 37). In the experimental group, a heating pad was applied on the patient's sacrum during the urodynamic study. All patients completed the State‐Trait Anxiety Inventory (20‐80) before and after the procedure and assessed their degree of pain and distress after the procedure by the visual analog scale (0‐10). Systolic and diastolic blood pressure and pulse rate were also checked before and after the procedure. Results: Demographic characteristics, mean age, procedure duration, pre and post‐procedural systolic, and diastolic blood pressures, and pulse rate were statistically similar between the experimental and control groups. The mean State‐Trait Anxiety Inventory was significantly lower in the experimental group than in the control group (30.9 ± 7.5 vs 42.5 ± 10.1, P < 0.001). The experimental group showed significantly lower pain and distress scores (Visual Analog Scale, 2.7 ± 1.5, 3.0 ± 1.5) compared with the control group (4.0 ± 1.6, 4.7 ± 2.0, both P < 0.001). Conclusions: Using a heating pad for female patients with stress urinary incontinence during a urodynamic study is a simple, economical, and effective therapy that enhances patient comfort and decreases anxiety, pain, and distress.